America and the art of Flanders : collecting paintings by Rubens, Van Dyck, and their circles - Quodbach, Esmée; Quodbach, Esmée (The Frick Collection studies in the history of art collecting in America, 2020)
Introduction : pleasure and prestige : the complex history of collecting Flemish art in America / Arthur K. Wheelock, Jr. -- Before modern connoisseurship : Robert Gilmor, Jr.'s, quest for Flemish paintings in the Early Republic / Lance Humphries -- Collecting the art of Flanders in antebellum New York / Margaret R. Laster -- The American Van Dyck / Adam Eaker -- A family affair : Bruegel and sons in America / Louisa Wood Ruby -- In search of major masters : Boston's history of collecting Flemish baroque painting / Ronni Baer -- "Never a dull picture" : John Graver Johnson collects Flemish art / Esmée Quodbach -- Creating an acquired taste for Flemish paintings : the advice of W.R. Valentiner and others / Dennis P. Weller -- Collecting seventeenth-century Flemish paintings in the Midwest / George S. Keyes -- From personal treasures to public gifts : the Flemish painting collection at the National Gallery of Art / Alexandra Libby -- Collecting Rubens in America / Marjorie E. Wieseman -- "It is a great painting for a museum" : collecting Flemish paintings in southern California / Anne T. Woollett.